Human posture recognition database and preprocessing simulation results - Htike, Kyaw Kyaw; Khalifa, Othman Omran; Abdallrahim, Rashid; Lai, Weng Kin (IIUM Press, 2011)
For Illlining and evaluatiun stage. damselS of re·processed posture image. are needed. In order to oblain tbem. video &equences ha~e to be recorded and preprocessed. The fonmlof ,'ideo fil•• produced by the video camera is Q",'ckTime. Vid.o File with the extension of ~.MOVM. However. Ihe problem i~ !hat the Quickl'm. Video I'i/e is nO! ~uPP'-'rted by any of the MA1l.AB videu input/OUtput (I/O) functions